Children Of Men (2006): Representation of Modern Spirituality in an Apocalyptic Dystopian World - Ovira Lestari, Mulya Cindi; Kristianto, Bayu (Udayana Journal of Social Sciences and Humanities; Vol 4 No 1 (2020): UJoSSH, February 2020, 2020)
In the post-industrialization era, spirituality has gone through many shifts. Specifically, perceptions of spirituality have changed for the worst after 9/11, which inspired several movies in portraying spirituality within the society in science fiction movies. Children of Men (2006) is one of science fiction movies that portray biblical apocalyptic narratives in which spirituality is a crucial element in the movie, indicating how influential spirituality is in popular culture. This research paper aims to analyze how modern spirituality is represented through the shift from Weber's concept of disenchantment to Jenkin's concept of re-enchantment, examining how it affects oneself in the biblical apocalyptic narrative. The representation is analyzed by focusing on a huge alteration that resulted from the attack of 9/11, which affects how the disenchanted society in the movie deals with the gloom of apocalypse. These responses lead to re-enchantment as the movie incorporates biblical allegories that represent hope for tomorrow, which is fundamental teaching for most religions.